CMOS Single Chip Fast Frequency Hopping Synthesizers for Wireless Multi-Gigahertz Applications Design Methodology, Analysis, and Implementation CONCLUSION AND FURTHER WORK - Bourdi, Taoufik; Kale, Izzet (Springer, 2007)
[Abstract Not Available]